The Legal Position of Digital Forensic Experts in the Settlement of Information Technology Crime Cases - Indriati Amarini; Rizky Aulia Cahyadri; Maulida Ayu Fitriani; Noorfajri Ismail (Faculty of Law, Universitas Negeri Semarang, Indonesia, 2024)
Indexed by Scopus